Perception on the Adoption of WhatsApp for Learning amongst University Students’ - Abubakar, Abdullahi Ismaila (International Journal of Research in STEM Education, 2021)
This paper Ã¢â‚¬Å“perception on the adoption of WhatsApp for learning amongst two hundred level curriculum and instruction I students of Sokoto State University, NigeriaÃ¢â‚¬Â was guided by three objectives, three research questions. The researcher used descriptive survey research design in the study. The researcher used qualitative method with the use of individual interview for data collection. Random sampling technique was employed to select the sample. The entire sample that was chosen is 10. The instruments used for data collection was data-blank. Coding system was applied to gather and interpreted data. The results indicated that majority of students used WhatsApp for learning, poster that WhatsApp is very easy to operate for learning and also shows that the attitude of students towards the use of WhatsApp for learning is positive. The research manifested that WhatsApp may be accepted as instructional tool in teaching and learning. Keywords: WhatsApp; Learning; Social media; E-learning.